Respuesta :

Answer:

Step-by-step explanation:

12). By applying Pythagoras theorem in the given right triangle,

      Hypotenuse² = (Leg 1)² + (Leg 2)²

      x² = 7² + 7²

      x² = 2(7)²

      x = [tex]\sqrt{2(7)^{2} }[/tex]

      x = [tex]7\sqrt{2}[/tex]

13). By sine rule,

      sin(60)° = [tex]\frac{\text{Opposite side}}{\text{Hypotenuse}}[/tex]

      [tex]\frac{\sqrt{3}}{2}=\frac{9\sqrt{3} }{y}[/tex]

      y = [tex]\frac{18\sqrt{3} }{\sqrt{3} }[/tex]

      y = 18

      By cosine rule,

      cos(60)° = [tex]\frac{\text{Adjacent side}}{\text{Hypotenuse}}[/tex]

      [tex]\frac{1}{2}=\frac{x}{y}[/tex]

      x = [tex]\frac{y}{2}[/tex]

      x = [tex]\frac{18}{2}=9[/tex]

14). By applying Pythagoras theorem in the given right triangle,

      12² = x² + x²

      144 = 2x²

      72 = x²

      x = √72

      x = 6√2